DANOS DE PERCEVEJOS PENTATOMÍDEOS (HETEROPTERA: PENTATOMIDAE) NAS CULTURAS DA SOJA E DO MILHO NA REGIÃO CENTRO-SUL DO PARANÁ - Bridi, Marcelo (2012)
Studies in greenhouse and in field about damage of Euschistus heros (Fabr, 1974) (Heteropetra: Pentatomidae) on soybean [Glycine max (L.) Merrill] and Dichelops melacanthus (Dallas, 1851) (Heteroptera: Pentatomidae) on corn [Zea mais (L.)] were conducted in the region of Guarapuava, State of Parana. The general objective of the study was determine the level of economic damage these pests in crop, and to elucidate the damage to the components of productivity. For soybean crop, the experiments were performed testing different populations and different times of infestation (growth stages) of this insect, so that at the growth stages tested in this study, it was found that infestations at R5 caused the highest damage, both in grain quality and yield. Among the insect population tested, none of them caused damage to soybean crop, that isuntil 8 bugs m-2 this insect was not harmful for the crop, and thus it could not be determined the level of economic damage of this insect to the crop. Therefore, studies with larger populations than that used in this study are necessary for determination of the level of economic damage. For the corn crop, effects of different insect population on the initial growth and on the yield components were studied. It was observed that 1 bug m-2 already caused significant damage at early growth stage of corn plants, and yield components were affected by 2 and 4 bugs m-2, and the economic injury level for this insect under the conditions of this study was 0.27 bugs m-2.